Pengembangan E-Book Bergambar untuk Mencegah Perilaku Bullying di SMP Negeri 53 Palembang - Berliana Rupita Arif; Taty Fauzi; Erfan Ramadhani (Journal on Education, 2024)
Currently, the development of technology is so rapid, especially in the world of education, it is caused by the emergence of technological developments in the process of managing resources and increasingly advanced human intelligence. Based on this, the researcher will develop an information service media, namely illustrated e-books to prevent bullying behavior. The problem in this study is that there is still a tendency of bullying that occurs in schools and a lack of electronic media in providing information services. The purpose of this study is to determine the feasibility and validity of the developed product. This type of research uses a development model (research & development), using the 3D model. Data collection techniques using questionnaires and observations. The data analysis technique uses validity and practicality analysis. Based on the results of media expert validation of 100% and linguist validation of 80%. It can be concluded that the illustrated e-book to prevent bullying behavior developed is suitable for use.